Report on the westerm Nay-Aru Valley and suggestions : irrigation in the Northern Province, Villankulam District - Parker, Henry, Irrigation Officer, Sri Lanka (Sessional papers ;, 1887)
Report submitted to the Parliament of Sri Lanka.